Pengaruh Teknologi Blockchain Terhadap Model Bisnis Tradisional: Potensi dan Tantangan - Siske Tontong; Hugo Prasetyo Winotoatmojo; Clora Widya Brilliana; Dyah Ayu Suryaningrum; Tribowo Rachmat Fauzan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to determine the influence of blockchain technology on traditional business models: potential and challenges. Through quantitative methods with a descriptive approach. Data collection techniques used are questionnaires, interviews, observations and written notes. Then analyzed using statistical methods. Descriptive and inferential statistical data analysis methods. The findings in this study are that blockchain technology has significant potential and benefits for traditional businesses, including increasing operational efficiency, data security, transparency and accountability, and reducing operational costs. However, the implementation of blockchain technology is highly dependent on the ability of traditional businesses to overcome several challenges such as regulatory compliance challenges, acceptance and adaptation, smart contract implementation, and interoperability.